MENINGKATKAN KEMAMPUAN SISWA DALAM MEMPRODUKSI TEKS HASIL OBSERVASI MELALUI VISUALISASI RUMOH ACEH DI SMA NEGERI MODAL BANGSA - Hasniyati, Hasniyati; Erwandi, Novia; Kurniawati, Rizki (Jurnal Dedikasi Pendidikan, 2024)
This research aims to improve students' ability to produce text observation result throught the visualization of Rumoh Aceh. This study uses a quantitative approach. Data collection techniques using tests. Data analysis was carried out, namely data reduction, data presentation, and drawing conclusions. Based on the research results, it was found that students' ability to produce text observation result throught visualization of the Aceh rumoh had increased. This is shown based on data obtained during the research. 1) Students have high ability to produce observation report text through visualization of Rumoh Aceh, both from the aspect of knowledge and writing skills. 2) Students demonstrate the ability to think critically, problem solve, creativity and innovation in accordance with the demands of the 21st century. 3) Students are able to work together, communicate and respect differences of opinion in the learning process. 4) Selection of teaching materials that are interesting and relevant to the object being observed plays an important role in improving student learning outcomes.